REDUCING SULPHATE AND NATURAL ZEOLITE IN Mn METAL SEDIMENTATION USING BACTERIA CONSORTIUM - Nur'aini Purnamaningsih; Endah Retnaningrum; Wahyu Wilopo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2017)
The objective of this study were determining the effects of natural zeolite from Wonosari on the activites of Sulfate Reducing Bacteria in Mangan (Mn) sedimentation of continous culture scale, and identifying the biofilm character of Sulfate Reducing Bacteria on consortium activites on natural zeolite using continous culture scale. The first studies was activation of zeolites, followed by testing the activity of consortium activities of Sulfate Reduction Bacteria in continuous culture scales; and biofilm characterization of Sulfate Reducing Bacteria consortium. The consortium of Sulfate Reducing Bacteria derived from goat feces. The size of zeo natural zeolites used in the consortium activity test of Sulfate Reducing Bacteria in Mangan sedimentation was 0.8 to 1.2 cm. The results showed that the consortium of Sulfate Reducing Bacteria in the bioreactor with the addition of zeolite had an activity that was more effective than the bioreactor without the addition of zeolite, where the pH was increased to pH 6.9; Mangan sedimentation was 61,16%, and the higher MPN index. Zeolite in a bioreactor with biofilm formation in 5th days and 9th days seems that there were biofilm consortium of Sulfate Reducing Bacteria growing attached to the surface of the zeolite.